Про перспективність дослідження пізньопалеолітичних пам’яток Криму - Колосов, Ю.Г. (Археологія, 1991)
У статті йдеться про відкриття Кримською палеолітичною експедицією Інституту археології АН УPCP на початку 80-х років пізньопалеолітичних стоянок, розташованих уздовж річок Криму на першій надзаплавній терасі. Якщо майбутніми розвідками в тотожніх умовах буде знайдено нові пізньопалеолітичні стоянки, це явище можна буде вважати закономірним. Воно дасть змогу докорінно поліпшити вивчення пізньопалеолітичної проблеми в Криму. Одной из актуальнейших проблем в палеолитоведении Украины является исследование позднего палеолита Крыма. Объясняется этот повышенный интерес тем, что по сравнению с другими эпохами камня позднепалеолитических памятников в Крыму найдено мало. Работами Крымской палеолитической экспедиции Института археологии АН УССР удалось открыть ряд новых позднепалеолитических памятников, располагавшихся на первой надпойменной террасе крымских рек. Открытие их в ранее непредвиденных топографических условиях размещения дает возможность дальнейших открытий, их раскопок и накопления материалов для решения проблемы позднего палеолита, и, в первую очередь, наиболее важных: перехода от мустье к позднему палеолиту, его сложения и развития, генетическую связь с мезолитом и пр. Investigation of the Late Paleolith in the Crimea is one of the most urgent problems in the study of Ukrainian Paleolith. This top interest to the problem is explained by the fact that only few Late Paleolithic relics are found in the Crimea as compared to other stone epochs. Works of the Crimean Paleolithic expedition of the Institute of Archaeology of the Ukr. SSR Academy of Sciences help to reveal a number of new late Paleolithic relics on the first overflood-plain terrace of the Crimean rivers. Being found under the unforeseen topographical conditions, they promote further discoveries, excavations and accumulation of materials to solve the Late Paleolithic problems and, in the first place, the most important ones: transition from the Mustier to Late Paleolithic, its formation, development genetic relation with Mesolith and soon.